Talat Paşa’nın ölümünün 81. yıldönümünde uluslararası terörizme bir bakış sempozyumuna sunulan bildiriler : 15 Mart 2002, İstanbul = Proceedings of the international symposium : the 81. anniversary of Talat Pasha’s assassination : a look on international terrorism : 15 March 2002, Istanbul (İstanbul)
ii, 183 s.